The Advantages of Prambanan Temple Existence and Its Conservation - Momentya Irsha Emeralda (Journal of Business on Hospitality and Tourism, 2015)
Prambanan tourist numbers continue to increase dramatically from year to year, which causes Prambanan temple always swamped with visitors. This is feared to adversely affect the sustainability of Prambanan. The temple area must be maintained and preserved its existence from being damaged in order to Prambanan can always provide benefits not only for economic activities, but also in tourism activities. The existence of Prambanan Temple provides benefits to the community, education, and also tourism in Indonesia. Because the number of Prambanan Temple visitors increasing significantly, conservation efforts are needed so that the existence of Prambanan remain stable and undamaged.